Responsibility as a Representation of the Architecture of the Internal Individual World - Baranova, Svitlana V. (Psychological Prospects Journal, 2017)
The article presents a theoretical analysis of representation features of the internal world as a responsibility or irresponsibility of the individual. It has been revealed that in conditions of social instability, volatility, risk and uncertainty in decision-responsibility becomes a way of self-protection of the subject from uncertainty as a possible method of risk management. It is considered that the subjective reality in the form of mental images or stories of events,   relations that are meaningful to the person as architectural structures which are created in the internal world. All these internal social structures are multivalued and multidimen- sional. The quality of the active inclusion of the individual in a particular social situa- tion depends on how the subject will recognize it, be going to overcome and interpret. It indicates that the internal world of a person can be considered as a verbal metaphor that defines the internal reality of the subject. It is proved that person consciously takes or does not take responsibility for his own vision of the “real” image, activities or relations to its implementation only under the condition of building and realizing his internal world. Then the person acts as a builder or a creator of his own stories, images and relationships. In this way a person creates architecture of his own life. Presented analogy of the architectural construction makes it possible to compare the work of the internal world of different people with the city's architectural structure.Key words: the maturity of the person, the internal world architecture, introjection, responsibility, representation.